Subsidies to the history of the German-speaking immigration to the province / State of S\~ao Paulo, Brazil (1840-1920) - Bruno Gabriel Witzel de Souza (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2016)
This paper proposes a chronology for the German-speaking immigration to S\~ao Paulo, Brazil (1840-1920) by identifying four main types: (i) spontaneous individual immigration; (ii) specialized laborers in public works, mainly road construction; (iii) indentured laborers in the plantations, mainly under the sharecropping system; (iv) settlers in official and private rural colonies. In the sequence, the immigration waves of the last two types are studied in detail, showing how they interconnected over time and how similar their processes of integration were. Such chronology aims to provide a framework for future studies about immigration waves to S\~ao Paulo, in general, and of German-speakers, in particular, complementing two strands in the literature. First, it provides a more dynamic perspective for the classical literature on the history of labor contracts, which is indirectly related to the immigration of German-speakers, but static in listing episodic events related to the latter. Second, it frames, under a more general perspective, specialized studies focused on specific impacts of the immigrants, such as current monographs about the history of education and German schools/institutions.
Keywords: 330; German-speaking immigrants; immigration; coffee plantations; sharecropping; official colonies